Software process simulation—at a crossroads?. Issue 10 (15th October 2014) - Zhang, He; Raffo, David; Birkhöltzer, Thomas; Houston, Dan; Madachy, Raymond; Münch, Jürgen; Sutton, Stanley M; Huang, Liguo; Armbrust, Ove
ABSTRACT Software process simulation (SPS) has been evolving over the past two decades after being introduced to the software engineering community in the 1980s. At that time the SPS technology attracted a great deal of interest from both academics and practitioners in the software process community—even to the extent of being one of the recommended techniques for achieving multiple Key Process Areas of Level 4 of the Capability Maturity Model Integration. However, in recent years, the growth of SPS seems to have slowed along with the number of reported applications in industry. This article summarizes the special panel that was held during ICSSP 2012 whose goals were to assess whether this technology remains applicable to today's software engineering projects and challenges and to point out the most beneficial opportunities for future research and industry application. Copyright © 2014 John Wiley & Sons, Ltd.